ANALISIS TINGKAT PENERAPAN NILAI-NILAI PANCASILA DALAM LINGKUNGAN SEKOLAH DASAR SDN 4 SIMPEN - Intan Nur Azizah, Neng; Jenal Mutaqin , Ejen; Fajar Suryaningrat, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is driven by the importance of internalizing Pancasila values as a moral foundation and national identy for elementary school student. The primary issue identifiend is the challenge in effectively instilling these values and the necessity for a concrete evaluation of how they are manifested in student behavior. This study aims to analyze the implementation level of Pancasila values within the environment of SDN 4 Simpen through a quantitative approach with a descriptive survey design. The research population consists of all 36 sixth-grade students at SDN 4 Simpen, with sampling conducted using a total sampling technique. Data were gathered through a questionnaire instrument developed based on empirical indicators such as religiosity, humanity, unity, democracy, and social justice, which were subsequently analyzed using descriptive statistics. The findings indicate that the implementation of Pancasila values at SDN 4 Simpen has been executed effectively. The majority of respondents fall into the moderate category, accounting for 80.56% (29 students), while the remaining 19.44% (7 students) have reached the high category. A crucial finding in this study is the absence of students in the low category (0%), proving that all research subjects possess adequate standards of moral understanding and behavior. The dominance of the moderate category suggests that while the foundation of character has been established, more innovative pedagogical strategies and habituation are required to accelerate the consistency of value implementation toward an optimal level.